Molecular cloning of the myo-inositol oxygenase gene from the kidney of baboons - González Álvarez, Rafael; Pérez Ibave, Diana Cristina; Garza Rodríguez, María de Lourdes; Lugo Trampe, Ángel; Delgado Enciso, Iván; Tejero Barrera, María Elizabeth; Martínez de Villarreal, Laura Elia; Garza Guajardo, Raquel; Sánchez Chaparro, María Marisela; Ruiz Aymá, Gabriel; Barboza Quintana, Oralia; Barrera Saldaña, Hugo Alberto; et al. (Spandidos Publications, 2017)
Abstract. The enzyme myo-Inositol oxygenase (MIOX) is also termed ALDRL6. It is a kidney‑specific member of the aldo‑keto reductase family. MIOX catalyzes the first reaction involved in the myo‑inositol metabolism signaling pathway and is fully expressed in mammalian tissues. MIOX catalyzes the oxidative cleavage of myo‑Inositol and its epimer, D-chiro-Inositol to D-glucuronate. The dioxygen-dependent cleavage of the C6 and C1 bond in myo‑Inositol is achieved by utilizing the Fe2+/Fe3+ binuclear iron center of MIOX. This enzyme has also been implicated in the complications of diabetes, including diabetic nephropathy. The MIOX gene was amplified with reverse transcription‑polymerase chain reaction from baboon tissue samples, and the product was cloned and sequenced. MIOX expression in the baboon kidney is described in the present study. The percentages of nucleotide and amino acid similarities between baboons and humans were 95 and 96%, respectively. The MIOX protein of the baboon may be structurally identical to that of humans. Furthermore, the evolutionary changes, which have affected these sequences, have resulted from purifying forces.